Identification of AB‐FUBINACA metabolites in authentic urine samples suitable as urinary markers of drug intake using liquid chromatography quadrupole tandem time of flight mass spectrometry. Issue 9 (11th November 2015) - Vikingsson, Svante; Gréen, Henrik; Brinkhagen, Linda; Mukhtar, Shahzabe; Josefsson, Martin
Abstract : Synthetic cannabinoids are a group of psychoactive drugs presently widespread among drug users in Europe. Analytical methods to measure these compounds in urine are in demand as urine is a preferred matrix for drug testing. For most synthetic cannabinoids, the parent compounds are rarely detected in urine. Therefore urinary metabolites are needed as markers of drug intake. AB‐FUBINACA was one of the top three synthetic cannabinoids most frequently found in seizures and toxicological drug screening in Sweden (2013–2014). Drug abuse is also reported from several other countries such as the USA and Japan. In this study, 28 authentic case samples were used to identify urinary markers of AB‐FUBINACA intake using liquid chromatography quadrupole tandem time of flight mass spectrometry and human liver microsomes. Three metabolites suitable as markers of drug intake were identified and at least two of them were detected in all but one case. In total, 15 urinary metabolites of AB‐FUBINACA were reported, including hydrolxylations on the indazole ring and the amino‐oxobutane moiety, dealkylations and hydrolysis of the primary amide. No modifications on the fluorobenzyl side‐chain were observed. The parent compound was detected in 54% of the case samples. Also, after three hours of incubation with human liver microsomes, 77% of the signal from the parent compound remained. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Three urinary metabolites of AB‐FUBINACA, detected in authentic case samples and after human liver microsome incubation, were identified as potential urinary markers of an AB‐FUBINACA intake. Also, parent drug was detected in 15 of 28 samples, possibly due to a slow metabolism of AB‐FUBINACA.